2010
DOI: 10.1371/journal.pone.0015802
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Reaction to Viewing Faces of Opposite- and Same-Sex Romantic Partners

Abstract: We pursued our functional magnetic resonance imaging (fMRI) studies of the neural correlates of romantic love in 24 subjects, half of whom were female (6 heterosexual and 6 homosexual) and half male (6 heterosexual and 6 homosexual). We compared the pattern of activity produced in their brains when they viewed the faces of their loved partners with that produced when they viewed the faces of friends of the same sex to whom they were romantically indifferent. The pattern of activation and de-activation was very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 34 publications
5
71
1
2
Order By: Relevance
“…This assumption is consistent with recent imaging studies, which showed no differences in response to the attachment target between homosexual and heterosexual men (37), and with our finding that homosexual and heterosexual fathers did not differ in their masculinity and femininity scores. Findings for all fathers that degree of amygdala-STS connectivity was associated with the amount of direct childcare responsibility further supports the hypothesis that our results describe human fathers' brain adaptation to caregiving activities.…”
Section: Discussionsupporting
confidence: 94%
“…This assumption is consistent with recent imaging studies, which showed no differences in response to the attachment target between homosexual and heterosexual men (37), and with our finding that homosexual and heterosexual fathers did not differ in their masculinity and femininity scores. Findings for all fathers that degree of amygdala-STS connectivity was associated with the amount of direct childcare responsibility further supports the hypothesis that our results describe human fathers' brain adaptation to caregiving activities.…”
Section: Discussionsupporting
confidence: 94%
“…However, a few areas were differentially activated too, including parts of the forebrain that have been implicated in drug-use addiction (Fisher et al, 2006). Additionally, Zeki and Romaya (2010) found that patterns of brain activity of subjects in love did not differ depending on sexual orientation, either for males or females.…”
Section: Imaging Romance and Sexmentioning
confidence: 96%
“…and Chinese participants (e.g., Xu et al, 2011;Zeki & Romaya, 2010) despite considerable literature on differences in self-reported experiences (e.g., Dion & Dion, 1993;Gao, 2001;Hatfield & Sprecher, 1995;Pines, 2001;Sprecher et al, 1994).…”
Section: Discussionmentioning
confidence: 99%